A review of the assessment tools used to evaluate whether medicines are prescribed rationally or not. Issue 5 (22nd April 2012) - Alosaily, Y; Conroy, S; Choonara, I
Abstract : Objective: The rational use of medicines is recognised as important by the WHO.1 It is important that medicines are used in children safely, effectively and in the most economic way. The authors wished to identify the assessment tools used in previous work to evaluate whether medicines are prescribed rationally in order to inform assessment of whether medicines are prescribed rationally for children in the UK. Methods: A literature search was performed in MEDLINE, EMBASE and PUBMED up to 2010. Criteria for inclusion in the review were (1) studies that used assessment tools for evaluating the prescription of medicines, (2) adults or children, (3) hospitals or primary healthcare, outpatients or inpatients. Results: 36 studies were found, involving 24 countries. 26 were carried out in low and lower middle income countries and only five in high income countries. 22 studies evaluated prescription medicines using WHO and International Network for Rational Use of Drugs (INRUD) indicators.2 These consisted of three types of indicators: (1) prescribing, for example number of drugs prescribed per consultation; (2) patient care for example mean consultation time, (3) health facility, for example availability of medicines from essential drugs list. All 22 studies were conducted in low income countries. Eight studies used modifications of the WHO and INRUD indicators. Five studies used their own guidelines or other criteria for assessing prescription medicines. One study evaluated prescription medicines by using the Essential Drug List. There were only four studies that involved children. Conclusions: Most studies used WHO and INRUD indicators in evaluating prescription medicines and were carried out in low income countries. There have been relatively few studies in high income countries or in children. There is a need for better assessment tools to evaluate whether medicines are used rationally.